The scattering of scalar fields in the Newtonian approximation. Issue 1 (10th February 2021) - Chen, Jian‐Ling; Gao, Zhi‐Fu; Li, Yong‐Hong; Ma, Zi‐Wei
Abstract: In this paper, by using a perturbation theory, we evaluate the scattering solution to Schrödinger equation under the Newtonian gravitational potential. We find that the scattering amplitude f ( θ ) depends on the potential U, which is composed of the external part U ex and the internal part U in, respectively. The above results are related to the mass density of a rotating Maclaurin spheroid. In the future, we will further analyze the sensitivity of scattering amplitude to the change of average mass density of the spheroid.